Kontribusi Hermeneutika Filosofis dalam Memahami Sastra Arab Pra Islam (Kajian Kritis Sastra Arab Pra Islam) - Rahmad Ari Wibowo (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2022)
Abstract This article addresses on hermeneutika Philosophical Hans Geoge Gadamer in understanding of Islamic pre-Arab literature. Hermeneutika Gadamer contributes to the meaning of literary text of Arabs that have the value the spirit of fighting in the creation of Arab ignorant and society Arab ignorant in the grammatical of literature in the grammatics. The process of diging the meaning of texts Arab literature forgiving. Understand, explaining and reveals the meaning of Arab literary text in the theory hermeneutika Gadamer must be interpretation of dialogue with Arab literary text Ignorant. That is the interpretation of interesting text of Arab literary text into the world of contemporary interpretation tradition. Arab texts will only live if understood, interpreted, and invited the dialogue with her readers.Arab text will only mean enriching meaning in the interpretation of Arab literary text. Thus enriches the meaning of Arab literary text. The results of the work of hermeneutika Gadamer in excavation the meaning of Arab literary text if pulled in the world of contemporary interpretation is to inherit the spirit of making literature and the intelligence of the ignorant. Although currently the spirit makes literature in the moderntera began to become extinct.